Exploring the impact of olive cake enrichment on wheat flour bread: A comprehensive study on quality parameters and nutritional enhancement - Kovač, Boris; Martina, Avbelj; Polak, Tomaž; Možina, Sonja Smole; Šporin, Monika (Food science & technology, 2025)
This study investigates the potential of incorporating olive cake (OC), a byproduct of olive oil production, as an ingredient in bread. OC originates from the Bianchina olive variety, which is dominant in the North Adriatic region and known for its resistance to low winter temperatures due to its high levels of phenolic compounds. OC is rich in caffeic acid (4.27 mg/kg) and ferulic acid (0.20 mg/kg), and it significantly enhances the final bread's total phenolic content from 10.4 mg GAE/kg in control to 39.8 mg in bread with 15% OC. Additionaly, it boots antioxidant activity, as expressed by FRAP from undetectable in control to 88.4 mg TE/kg in the bread with 15% OC. The baking process slightly increased the DPPH inhibition ratio but reduced the concentration of some phenolic antioxidants such as ferulic acid, vanillic acid, catechin, and luteolin. The incorporation of OC decreased leavening and significantly reduced the bread's volume and specific volume, indicating higher density. Bread with 6% OC exhibited reduced firmness after 24 h compared to the control, thereby improving initial texture quality. OC addition also darkened the crumb color, with the effect being more pronounced at higher concentrations. While OC addition did not significantly enhance insoluble dietary fiber, it notably increased the final soluble dietary fiber content from 0.67 g/100 g in the control to 1.58 g/100 g in the enriched bread. OC significantly influenced most sensory parameters, increasing bitterness, aftertaste, off-taste, and flour intensity, particularly at the 15% OC level. A 6% OC level increased sweet taste and aroma, while sour taste was less pronounced. In conclusion, the findings suggest that olive cake can be a valuable ingredient for functional bread products, effectively balancing health benefits with sensory characteristics. These results highlight the potential for utilizing olive cake in line with circular economy principles, paving the way for the development of fortified foods. •Olive cake (OC) is a byproduct of olive oil production, rich in bioactive compounds and antioxidants.•OC can be incorporated into bread on sustainable mode without the need for extraction or energy-intensive pretreatment.•The reformulated bread resulted in good sensory acceptance, despite a significant reduction in the bread's specific volume.•The final product retained the bioactive properties of OC throughout the baking process.